LEGAL PROTECTION OF CHILDREN IN CONFLICT WITH THE LAW IN INVESTIGATION PROCESS THROUGH RESTORATIVE JUSTICE (CASE STUDY OF BALIKPAPAN CITY RESORT POLICE) - Alex Bhirawa; Indra Gunawan Purba; Muhammad Faisal (LPPM YPITI, 2026)
Investigation through a restorative justice approach to children is an effort to resolve criminal cases involving children by emphasizing the restoration of relationships between perpetrators, victims, and society, not just punishment. The legal regulation of restorative justice against children as perpetrators of criminal acts is regulated in Law No. 11 of 2012 concerning the Juvenile Criminal Justice System. The implementation of restorative justice as a protection for children in conflict with the law as perpetrators of sexual intercourse crimes in the Balikpapan City Resort Police is to focus on the needs of victims, perpetrators of crime, and also involve community participation.